The Problematics of Learning Indonesian Literature in the Pandemic Era at Islamic Junior High School 1 Ternate City - Sasmayunita; Hubbi Saufan Hilmi (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This study aims to describe the problems in learning Indonesian Language and Literature during the Islamic Junior High School 1 Ternate City pandemic. The method used in this research is qualitative, with the research location in Islamic Junior High School 1 Ternate City. The data in this study are the results of observations about the process of learning literature in Islamic Junior High School 1 Ternate city. Data collection techniques in this study are observation, documentation, and interviews. The data that has been collected is analyzed in several stages, including data reduction, data presentation, member checks, and conclusion. The results showed that the problems of learning literature in Islamic Junior High School 1 Ternate city were caused by some factors. They are the unprepared implementation of the online teaching and learning process, inadequate devices, the high price of data packages for eastern Indonesia, the lack of enthusiasm of students in online learning, and the mastery of science and technology among teachers, which is not sufficient. In addition, problems in learning literature arise due to the lack of innovative and creative teachers in applying learning methods, learning media, and students reading interest in reading materials in the form of literary works, which are still in the low category.